MODERN SOCIAL ENVIRONMENT AS A FACTOR AND A SOURCE OF INFORMATIONAL STRESS - Nina I. Medvedeva (Вестник Северо-Кавказского федерального университета, 2022)
The article focuses on the “informational stress” as an issue and the reason behind unstable psychological health in humans. There is also an attempt to identify the causes for the “information explosion” as a whole and the impact that information stress has on various layers of population in the nowadays Russia. The author also provides a description of the most typical informational overloads affecting people of different age groups.